(untitled) (Journal of the College of Basic Education, 2023)
In Persia, a new phase began in the relationship of the Persian government with the clergy, especially during the reign of the Shaheen (Muhammad Mirza bin Abbas Mirza and Nasir al-Din Mirza). The government began to establish a strange relationship with the clergy, and although the government pretended to support the clergy, it failed in the end Establishing a relationship with them, due to the extremism of the Shaheen (Muhammad Mirza bin Abbas Mirza and Nasir al-Din Mirza) who do not believe in the teachings of Islam, and it was difficult to agree between the government and the clergy, and as a result, many religious rebellions against the Persian government emerged during the period (1834-1852 AD).